Pelatihan peraturan perwasitan futsal bagi siswa MAN 1 Sinjai - Arifuddin Usman; Adam Mappaompo (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
This Devotion to the public was in implementing in the form of the introduction of the training and information about refereeing futsal students sinjai. 1 manThis event is aimed to: (1) introduce provisions concerning. futsal refereeing in the game;(2)enthusiastic and response to your students in training so that they are aware of the importance of provisions concerning futsal refereeing in the game;(3) understand the extent of understanding of students in training about rule futsal refereeing;(4)know that the changes in training about rule futsal refereeing in the game. Program activities devotion to the community is separated into two main activities which wereactivities description in theory done for one day that is explain that the rules refereeing in the game futsal and activities practice, done for 5 days. The devotion to people show that (1)the participants will receive matter by the willingness and so semangant matter is given about futsal refereeing regulation can be absorbed by all participants and capable of practiced well;(2)to increase knowledge and understanding the students about sports futsal especially concerning refereeing regulation is very high futsal considered very useful for themselves;( 3 )the capability of the students MAN 1 Sinjai in the practice of futsal refereeing regulationand(4) beneficiaries realized that material provided to add very useful insight for students MAN 1 Sinjai.